Pengaruh (CH2)n Terhadap Karakteristik Pembakaran Bahan Bakar Pelet Partikel Arang Sampah Organik - Mustiadi, Lalu; Astuti, Siswi; Eko Purkuncoro, Aladin (Prosiding SENTIKUIN (Seminar Nasional Teknologi Industri, Lingkungan dan Infrastruktur), 2019)
The effect of (CH2)n on the combustion characteristics of organic waste charcoal pelletfuel has been studied visually and experimentally on atmospheric pressure and roomtemperature. Organic waste charcoal particles containing (C, O, Mg, Al, Si, Ca), and plasticbottle oil are formed as polyethelin (CH2)n. Pellet fuel is made from a mixture of polyethelinand organic waste charcoal particles, based on a percentage of the mass ratio (1; 5; 10%). Thecharacteristics of pellet combustion are identified from the time and temperature signal of theflame, by igniting a pellet under the thermocouple junction. The results showed that theincreasing mass of the mixture had a stronger influence on the pellet combustion process,indicated by the faster start-up time with an increased pellet burning rate. The catalyst in theorganic waste charcoal binds hydrogen from (CH2)n, forming the molecular structure (CH2)n tobe weak with a low density, therefore it can quickly evaporate and burn. With the bigger massof the mixture, carbon moles in pellets are increasing. Consequently, the greater the mass ratioof the mixture will form wider energy absorption characteristic, forming an equilibriumstoichiometric reaction by producing an increased rate of combustion energy release. Theincreasing mass of the mixture, helps the generation of activation energy is greater in theburning of organic charcoal waste pellets, as confirmed by the greater absorption of infrared%T energy.